Robotic Versus Conventional Nipple-Sparing Mastectomy With Immediate Breast Reconstruction - Houvenaeghel, Gilles; Barrou, Julien; Jauffret, Camille; Rua, Sandrine; Sabiani, Laura; Van Troy, Aurore; Buttarelli, Max; Blache, Guillaume; Lambaudie, Eric; Cohen, Monique; Bannier, Marie (Frontiers in Oncology, 2021)
Background: Several studies reported feasibility and safety of robotic-NSM (R-NSM). The aim of our prospective study was to compare R-NSM and conventional-NSM (C-NSM). Methods: We analyzed patients operated, with and without robotic assistance (R-NSM or C-NSM) and immediate breast-reconstruction (IBR) with implant or latissimus dorsi-flap (LDF). The main objective was complication rate and secondary aims were post-operative length of hospitalization (POLH), duration of surgery and cost. Results: We analyzed 87 R-NSM and 142 C-NSM with implant-IBR in 50 and 135 patients, with LDF-IBR in 37 and 7 patients, respectively. Higher durations of surgery and costs were observed for R-NSM, without difference for POLH and for interval time to adjuvant therapy, between R-NSM and C-NSM. In multivariate analysis, R-NSM was not associated with higher breast complication rate (OR=0.608) and significant factors were breast cup-size, LDF combined with implant-IBR, tobacco and inversed-T incision. Grade 2-3 breast complications rate were 13% for R-NSM and 17.3% for C-NSM, significantly higher for LDF combined with implant-IBR, areolar/radial incisions and BMI>=30. A predictive score was calculated (AUC=0.754). In logistic regression, patient’s satisfaction between C-NSM and R-NSM were not significantly different, with unfavorable results for BMI >=25 (OR=2.139), NSM for recurrence (OR=5.371) and primary breast cancer with radiotherapy (OR=4.533). A predictive score was calculated. In conclusion, our study confirm comparable clinical outcome between C- NSM and R-NSM, in the price of longer surgery and higher cost for R-NSM. Predictive scores of breast complications and satisfaction were significantly associated with factors known in the pre-operative period.